The Selection of Trade Integration Indicators: Intraregional Share, Intensity, Homogeneous Intensity, and Introversion Index - Shintaro Hamanaka (Asian Development Bank (ADB), 2015)
This paper attempts to provide a clear and comprehensive picture of trade integration in Asia, using a trade linkage diagram. The paper reviews four types of indicators (share, intensity, homogeneous intensity, and introversion index) and argues that the introversion index is the most suitable indicator for the comparison of the level of trade integration, both in terms of cross-regional comparisons and time series analyses. Next, since Asia is a group of heterogeneous economies and the level of integration across subregions is not consistent, the paper includes a subregional analysis of trade integration in Asia. The analysis includes the (i) regional introversion of each subregion, (ii) intersubregional trade linkage, and (iii) extraregional trade linkage of each subregion. The subregional trade linkage diagram based on the introversion index provides us with a snapshot of trade integration, which is useful for both scholars and policy makers. At a glance, we can understand who trades more than others, and with whom.
hdl:11540/5184
Keywords: F14; F15; 330; intraregional trade share; introversion index; subregions; trade integration; trade linkagediagram